Model Pencegahan Penyalahgunaan Narkotika Berbasis Edukasi Hukum di Desa Riwo Kabupaten Dompu - Syamsuddin, Syamsuddin; Andriadin, Andriadin; Mardiah, Nurul Izzatil; Nurfadilah, Nurfadilah (IAIN Langsa, 2026)
This study aims to analyze and formulate a legal education–based drug abuse prevention model in Riwo Village, Dompu Regency, and to assess its implications for enhancing community legal awareness. This research employs field research with a qualitative socio-legal approach, utilizing in-depth interviews, observation, and document analysis. The findings indicate that a participatory and community-based legal education model effectively improves legal literacy, fosters internally driven legal compliance, and strengthens the role of local actors in drug abuse prevention. This model offers a more humanistic, contextual, and sustainable preventive approach for the development of village-level drug prevention policies.